The Iroquois (Iro/Irx) homeobox genes are conserved Hox targets involved in motor neuron development - Catarina Catela; Stavroula Assimacopoulos; Yihan Chen; Konstantinos Tsioras; Weidong Feng; Paschalis Kratsios (iScience)
Summary: The Iroquois (Iro/Irx) homeobox genes encode transcription factors with fundamental roles in animal development. Despite their link to various congenital conditions in humans, our understanding of Iro/Irx gene expression, function, and regulation remains incomplete. Here, we conducted a systematic expression analysis of all six mouse Irx genes in the embryonic spinal cord. We found that Irx1, Irx2, Irx3, Irx5, and Irx6 are expressed in specific groups of motor neurons (MNs). Further, we employed CRISPR-Cas9 gene editing to uncover essential but distinct roles for Irx2 and Irx6 in MN development. We also found that HOX proteins, which are conserved regulators of MN development across species, control Irx gene expression both in mouse and Caenorhabditis elegans MNs. Altogether, our study provides insights into Iro/Irx expression and function in the developing spinal cord and uncovers an ancient gene regulatory relationship between HOX and Iro/Irx genes.